MODEL-MODEL PENGEMBANGAN KURIKULUM DAN SILABUS PEMBELAJARAN BAHASA ARAB - Zubaidi, Ahmad (Cendekia: Jurnal Kependidikan dan Kemasyarakatan, 2015)
Abstract: Syllabus refers to a lesson plan on a particular or group of subjects/ themes that covers standard of competency, basic competencies, learning materials, learning activities, indicators of competence achievement, assessment, allocation of time, and learning resources. The principles in developing syllabus are scientific, relevant, systematic, consistency, adequate, actual and contextual, flexible, and comprehensive. The procedures of syllabus development are reviewing and determining standard of competency, assessing and determining basic competencies, determining indicators of competence achievement, identifying learning materials, determining the type of assessment, determining the allocation of time, and determining the source of learning. There are various models of syllabus on learning Arabic as a foreign language. Each model has a concept in teaching Arabic with its own framework and aspect of skills. ØŒØ©Ø¡Ø§ÙÙƒÙ„Ø§ Ø±Ø§ÙŠØ¹Ù… Ù‰Ù„Ø¹ Ù„Ù…ØªØ´ÙŠ Ù‰Ø°Ù„Ø§ Ø©Ù†ÙŠØ¹Ù„Ù…Ø§ Ø³ÙˆØ±Ø¯Ù„Ø§ Ù†Ù… Ø¹Ø¬Ù… ÙˆØ£ Ø§Ù… Ø©Ø¯Ø§Ù… ÙÙŠ Ù‡Ø¹ÙˆØ±Ø´Ù…Ùˆ Ø³ÙŠØ±Ø¯ØªÙ„Ø§ Ø¬Ù…Ø§Ù†Ø±Ø¨ ÙˆÙ‡ Ø±Ø±Ù‚Ù„Ù…Ø§ Ù†Ù…Ø²Ù„Ø§Ùˆ ØŒÙ…ÙŠÙˆÙ‚ØªÙ„Ø§Ùˆ ØŒØªØ§ÙŠØ§ÙÙƒÙ„Ø§ Ù‡Ø°Ù‡ Ù„Ù‰Ø¥ Ù„ÙˆØµÙˆÙ„Ø§ ØªØ§Ø±Ø´Ø¤Ù…Ùˆ ØŒØ³ÙŠØ±Ø¯ØªÙ„Ø§ Ø©Ø·Ø´Ù†Ø£Ùˆ ØŒØ³ÙŠØ±Ø¯ØªÙ„Ø§ Ø¯Ø§ÙˆÙ…Ùˆ ØŒØ©ÙŠØ³Ø§Ø³Ù„Ø£Ø§ Ø©Ø¡Ø§ÙÙƒÙ„Ø§Ùˆ Ø©Ø±ØµØ§Ø¹Ù„Ù…Ø§ ØŒØ©ÙŠØ¦ÙÙƒÙ„Ø§Ùˆ ØŒØ©ÙŠÙ…Ø¸Ù†Ù„Ù…Ø§Ùˆ ØŒØ©ÙŠØ¨Ø³Ø§Ù†ØªÙ„Ø§Ùˆ ØŒØ©ÙŠÙ…Ù„Ø¹Ù„Ø§ :ÙŠÙ‡ÙˆØ±Ø±Ù‚Ù„Ù…Ø§ Ù…ÙŠÙ…ØµØª ÙÙŠ Ø³Ø³Ø£ Ø©Ø«Ù…Ùˆ .Ø©Ø³Ø§Ø±Ø¯Ù„Ø§ Ø±Ø¯Ø§ØµÙ…Ùˆ ØŒØØ§ØªÙ„Ù…Ø§ ØŒØ©Ø¡Ø§ÙÙƒÙ„Ø§ Ø±Ø§ÙŠØ¹Ù… ÙŠÙ†ÙŠØ¹ØªÙˆ Ø©Ø³Ø§Ø±Ø¯ :ÙŠÙ‡ ÙŠØ³Ø§Ø±Ø¯Ù„Ø§ Ø±Ø±Ù‚Ù„Ù…Ø§ Ù…ÙŠÙ…ØµØª ØªØ§ÙˆØ·Ø® Ø§Ù…Ø£ .Ø©ÙŠÙ„ÙˆÙ…Ø´Ù„Ø§Ùˆ ØŒØ©ÙŠÙ†ÙˆØ±Ù„Ù…Ø§Ùˆ ØŒØ©ÙŠÙ‚Ø§ÙŠØ³Ù„Ø§Ùˆ ÙŠÙ†ÙŠØ¹Øª ØŒØ©ÙŠØ³Ø§Ø±Ø¯Ù„Ø§ Ø¯Ø§ÙˆÙ„Ù…Ø§ Ø´ÙŠØªÙØª ØŒØªØ§ÙŠØ§ÙÙƒÙ„Ø§ Ù‡Ø°Ù‡ Ù„Ù‰Ø¥ Ù„ÙˆØµÙˆÙ„Ù„ ØªØ§Ø±Ø´Ø¤Ù„Ù…Ø§ ÙŠÙ†ÙŠØ¹Øª ØŒØ©ÙŠØ³Ø§Ø³Ù„Ø£Ø§ Ø©Ø¡Ø§ÙÙƒÙ„Ø§ ÙŠÙ†ÙŠØ¹ØªÙˆ Ø©Ø³Ø§Ø±Ø¯ Ø©ÙŠØ¨Ø±Ø¹Ù„Ø§ Ø©ØºÙ„Ù„Ø§ Ù…ÙŠÙ„Ø¹ØªÙ„ ÙŠØ³Ø§Ø±Ø¯Ù„Ø§ Ø±Ø±Ù‚Ù„Ù…Ø§ Ù†Ù… Ø¹Ø§ÙˆÙ†Ø£ ÙƒØ§Ù†Ù‡ .Ø©Ø³Ø§Ø±Ø¯Ù„Ø§ Ø±Ø¯Ø§ØµÙ… ÙŠÙ†ÙŠØ¹Øª Ù…Ø« Ù†Ù…Ø²Ù„Ø§ Ø¯ÙŠØ¯ØªØ ØŒÙ…ÙŠÙˆÙ‚ØªÙ„Ø§ Ø¨ÙˆÙ„Ø³Ø£ Ù‡Ù„ Ù†Ø£ Ø¨Ù†Ø§Ø¨Ø¬ )Ø©ÙŠÙˆØºÙ„Ù„Ø§ ØªØ§Ø±Ø§Ù‡Ù„Ù…Ø§Ùˆ ( Ø©ÙŠØ¨Ø±Ø¹Ù„Ø§ Ø©ØºÙ„Ù„Ø§ Ù…ÙŠÙ„Ø¹Øª Ù‚ÙŠØ¨Ø·Øª ÙÙŠ Ù…ÙŠÙ‡Ø§ÙÙ… Ø¹ÙˆÙ†Ù„Ø§ Ø§Ø°Ù‡ Ù†Ù… Ù„ÙƒÙ„Ùˆ .Ø©ÙŠØ¨Ù†Ø¬Ø£ Ø©ØºÙ„Ùƒ .Ù‡ÙŠÙ„Ø¥ Ø¯Ù†ØªØ³ÙŠ Ø³Ø³Ø£ ÙƒÙ„Ø°Ùƒ